2015
DOI: 10.1039/c5ay00522a
|View full text |Cite
|
Sign up to set email alerts
|

Tracking single particle rotation: probing dynamics in four dimensions

Abstract: Direct visualization and tracking of small particles at high spatial and temporal resolution provides a powerful approach to probing complex dynamics and interactions in chemical and biological processes.Analysis of the rotational dynamics of particles adds a new dimension of information that is otherwise impossible to obtain with conventional 3-D particle tracking. In this review, we survey recent advances in single-particle rotational tracking, with highlights on the rotational tracking of optically anisotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 82 publications
(171 reference statements)
0
33
0
Order By: Relevance
“…Among them, the most widely used are rod-shaped particles, including gold nanorods (Gu et al, 2012, 2011; Neupane et al, 2016; Chaudhari and Pradeep, 2014; Xiao et al, 2011a), colloidal ellipsoids (Han et al, 2006; Mukhija and Solomon, 2007), quantum rods (Tsay et al, 2006; Ohmachi et al, 2012), filamentous viruses (Lettinga et al, 2005), and dumbbell particles (Uspal et al, 2013; Uspal and Doyle, 2014), Typically, the rotation of rod-shaped imaging probes can be measured along two of the three possible rotational axes: in-plane rotational angle φ and out-of-plane rotational angle θ (Fig. 1a) (Anthony and Yu, 2015). The third axis of rotation, longitudinal rotational angle δ around the long axis of a rod, is generally not visible unless optical anisotropy is created along the side of the rod.…”
Section: General Methods For Probing Rotational Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, the most widely used are rod-shaped particles, including gold nanorods (Gu et al, 2012, 2011; Neupane et al, 2016; Chaudhari and Pradeep, 2014; Xiao et al, 2011a), colloidal ellipsoids (Han et al, 2006; Mukhija and Solomon, 2007), quantum rods (Tsay et al, 2006; Ohmachi et al, 2012), filamentous viruses (Lettinga et al, 2005), and dumbbell particles (Uspal et al, 2013; Uspal and Doyle, 2014), Typically, the rotation of rod-shaped imaging probes can be measured along two of the three possible rotational axes: in-plane rotational angle φ and out-of-plane rotational angle θ (Fig. 1a) (Anthony and Yu, 2015). The third axis of rotation, longitudinal rotational angle δ around the long axis of a rod, is generally not visible unless optical anisotropy is created along the side of the rod.…”
Section: General Methods For Probing Rotational Dynamicsmentioning
confidence: 99%
“…However, a growing number of studies show that rotational dynamics are a prevalent and important feature in biological systems (Anthony and Yu, 2015). Noji et al (1997) performed an early study that directly observed the rotation of mitochondrial F 1 -ATPase during ATP hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of these rotational imaging methods can be found in a recent review from our group. 122 One strategy involves using Janus particles.…”
Section: Janus Particles As Imaging Probesmentioning
confidence: 99%